Performative citizenship and the politics of scale: Local, national and global citizenships in Zimbabwe. (October 2021) - Chipato, Farai
Abstract: This paper explores the interaction between different scales of governance and performative citizenship, understood as acts by citizens that claim new political rights and reshape the political arena. Performance allows citizens to creatively transform the meanings and functions of citizenship during struggles over rights. The paper focuses on a series of examples in Zimbabwe, which highlight the entanglement of different scales of citizenship and the ways that the acts of citizenship both challenge and sustain these relationships. This is examined through a framework that combines theories of performative citizenship with concepts from human geography that examine scales of governance. The argument draws out the implications of these dynamics in relation to conflicts over customary citizenship in rural Zimbabwe, the issue of dual citizenship among white Zimbabweans and the exercise of citizenship rights by non-Zimbabweans. It highlights both the ways in which citizens have harnessed the creative potential of acts of citizenship which address multiple scales, and the constraints that scalar hierarchies put on citizen action. The examples demonstrate that new forms of political rights can be produced across scales, but that opportunities for creative acts of citizenship are unevenly distributed due to these scalar hierarchies, which are produced by postcolonial legacies.